The econometrics of macroeconomic modelling - Eitrheim, O. (Oxford University Press, 2012)
This book is about building models by testing hypotheses of macroeconomic theories–rather than by imposing theories untested. This is quite a crucial distinction in macroeconometric model building. For an empirical model to be useful, be it as a basis for economic policy decisions or for forecasting, it needs to describe the relevant aspects of reality. Simplification is the main virtue of theoretical model building. In empirical modelling it might easily become a vice. A theoretical model is often reduced to just those equations that are required to make it work for the problem at hand. A good empirical model should also be able to explain problems that might occur. Einstein’s advice that ‘everything should be as simple as possible . . . but no simpler’ is as relevant as ever. If a model does not describe the data, it may just be too simple to be used as a tool for macroeconomic decision making.